Unraveling the bacterial diversity of Cangar Hot Spring, Indonesia by Next Generation Sequencing of 16S rRNA gene - Almando Geraldi; Chia Chay Tay; Ni’matuzahroh Ni’matuzahroh; Fatimah FATIMAH; Wan Nurhayati Wan Hanafi (Society for Indonesian Biodiversity, 2021)
Abstract. Geraldi A, Tay CC, Ni’matuzahroh, Fatimah, Hanafi WNW. 2021. Unraveling the bacterial diversity of Cangar Hot Spring, Indonesia by Next Generation Sequencing of 16S rRNA gene. Biodiversitas 22: 4060-4066. This study is the first attempt at using the Next Generation Sequencing (NGS) method with 16S rRNA to understand the bacterial community structure in an Indonesian hot spring. This study aims to unravel the bacterial diversity of the Cangar Hot Spring as one of the most explored natural hot springs in East Java, Indonesia. We found Proteobacteria and Bacteroidetes as the two most abundant phyla. We discovered the first occurrence of genera Cloacibacterium and Methylobacillus in the hot spring ecosystem, which was the most dominant genera at Cangar Hot Spring. We also found several potential bacteria for bioindustry and bioremediation, such as Acinetobacter junii and Pseudomonas alcaligenes. Besides that, we also observed opportunistic pathogens from genera Comamonas and Vogesella. This study result will provide valuable information for further bioprospecting of bacteria with commercial potential and the development of health and safety measures in the Cangar Hot Spring, among others. Hopefully, this report would encourage the use of NGS technology for studying other hot springs in Indonesia.